Development of an Injection Mold for Liquid Silicone Rubber Using Rapid Tooling Technology. Issue 3 (3rd July 2019) - Kuo, Chil-Chyuan; Lin, Jun-Xian
ABSTRACT: Rapid tooling (RT) technology can reduce the time to market for injection molded products compared to standard machining methods. Aluminum-filled epoxy resin molds can be used in place of conventional steel molds for small batch injection molding production. Liquid silicone rubber (LSR) parts are stable and used in many applications. To compress time to market for new injection molded products it is necessary to develop a mold swiftly and effectively. In this study, RT technology was used to make a mold with a heating element for LSR injection molding. The mold was fabricated from aluminum-filled epoxy resin and injection could be done after a mold warm-up time of 35 min – to stabilize mold surface temperature. The optimal process parameters were found to be: injection speed 50 mm/s, packing pressure 14 MPa, mold temperature 180°C, and packing time 12 s.